An inductively coupled plasma mass spectrometry method for relative free copper determination and generation of a paediatric reference interval. (July 2018) - Wainwright, P; Wadey, D; Cook, P
Background: Diagnosis of Wilson's disease is currently performed using caeruloplasmin as a first-line screening test; however, this test has well-described limitations. Monitoring of known Wilson's disease patients often uses 24-h urine collection; however, this is inaccurate in children. Methods for directly measuring plasma free copper have been described, but no reference interval data exist for a paediatric population. Methods: An inductively coupled plasma mass spectrometry method for measuring free copper was developed and validated, using ultracentrifugation. A paediatric reference interval was generated using 85 plasma samples from children attending outpatient clinics at University Hospital Southampton. Results: Results showed no significant contamination of copper using the ultracentrifugation technique, and validation showed the method was accurate and precise with an analytical coefficient of variation between 5 and 7% depending on the concentration of free copper. Conclusions: We describe the use and validation of an ultrafiltration inductively coupled plasma mass spectrometry method for plasma free copper with the first published paediatric reference interval. Free copper could provide much needed assistance for the monitoring of Wilson's disease in children and also for adults.